Fournier’s Acute Gangrene of The Male Genitals: Diagnosis and Treatment of a Surgical Emergency (British Journal of Multidisciplinary and Advanced Studies, 2025)
Fournier's gangrene is an acute pathological process of necrotizing fasciitis involving the male genitalia and the perineal region, often fulminant and rapidly progressive and with a high risk of morbidity and mortality. It is characterized by severe necrosis of loose tissues and in the majority of cases is due to a mixed infection of aerobic and anaerobic bacteria. It usually follows a genitourinary or anorectal - ischiorectal infection and presents predisposing factors such as diabetes mellitus, obesity or alcohol abuse. The syndrome is characterized by pain and especially by scrotal-genital swelling, also with the presence of exudative necrotic areas in the genitoperineal region. This serious pathology requires early diagnosis and timely treatment where the prognosis is often favorable if the therapy is synergic and multidisciplinary. In this work the Authors report a case of Fournier's syndrome of the male genitalia with the aim of describing the clinical, diagnostic and treatment aspects of this fearsome disease.